Biomimetic synthesis of pyrone-derived natural products: exploring chemical pathways from a unique polyketide precursor. - Eade, S; Walter, M; Byrne, C; Odell, B; Rodriguez, R; Baldwin, J; Adlington, R; Moses, J (2008)
Our biomimetic hypothesis proposes that families of diverse natural products with complex core structures such as 9,10-deoxytridachione, photodeoxytridachione and ocellapyrone A are derived in nature from a linear and conformationally strained all-( E) tetraene-pyrone precursor. We therefore synthesized such a precursor and investigated its biomimetic transformation under a variety of reaction conditions, both to the above natural products as well as to diverse isomers which we propose to be natural products "yet to be discovered". We also report herein the first synthesis of the natural product iso-9,10-deoxytridachione.